Self-rated health and changes in self-rated health as predictors of mortality: First evidence from German panel data - Johannes Schwarze; Hanfried H. Andersen; Silke Anger (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
Empirical evidence from several countries reveals that self-rated health is a valid predictor of mortality. So far, there have been no studies conducted for Germany. Using data from the German Socio-Economic Panel Study (GSOEP) we confirm the relationship between self-rated health and mortality for Germany. In addition the GSOEP data enable an exploration of the trajectory hypothesis.
Keywords: 330; Sterblichkeit; Prognoseverfahren; Gesundheit; Öffentliche Meinung; Schätzung; Deutschland